Study on Preferential Solvation of Water by Electrochemical Method. Issue 12 (25th July 2019) - Yan, Chunxia; Huang, Ximing; Chen, Jingchao; Guo, Haixia; Shao, Huibo
Abstract: The preferential solvation of water plays an important role in ferrocene research which is a subject of current interest. Voltammetric investigations were carried out for Au electrode in acetonitrile/water, showing preferential solvation of water. In our work, the preferential solvation of water in acetonitrile/water was studied by electrochemical methods including cyclic volitammetry, electrochemical impedance spectra and double‐step chronoamperometry. Ferrocenemethanol (FcCH2 OH) molecules as a solute spontaneously adsorb on the electrode surface in anhydrous acetonitrile, resulting from acetonitrile molecules tend to form an acetonitrile solvent layer on the surface of the electrode and acetonitrile solvent layer has a lower energy barrier than the aqueous solvent layer, which has been obtained by modeling solvation. The solvent strongly influences electrochemical behavior of solute. Once there is an amount of water in acetonitrile solvent, FcCH2 OH that adsorbed on the electrode surface desorb. This is because water preferentially solvate with FcCH2 OH in term of intermolecular forces between solvent and solute. Moreover, hydrogen bond between water molecules and FcCH2 OH molecules is stronger than dipole‐dipole interaction between acetonitrile molecules and FcCH2 OH molecules in solvation effect. Through electrochemical behavior of FcCH2 OH changing, preferential solvation of water is analyzed by electrochemical methods. Abstract :